Advances in metabolic engineering in the microbial production of fuels and chemicals from C1 gas - Humphreys, Christopher M.; Minton, Nigel P. (Elsevier, 2018)
The future sustainable production of chemicals and fuels from non-petrochemical sources, while at the same time reducing greenhouse gas (GHG) emissions, represent two of society's greatest challenges. Microbial chassis able to grow on waste carbon monoxide (CO) and carbon dioxide (CO2) can provide solutions to both. Ranging from the anaerobic acetogens, through the aerobic chemoautotrophs to the photoautotrophic cyanobacteria, they are able to convert C1 gases into a range of chemicals and fuels which may be enhanced and extended through appropriate metabolic engineering. The necessary improvements will be facilitated by the increasingly sophisticated gene tools that are beginning to emerge as part of the Synthetic Biology revolution. These tools, in combination with more accurate metabolic and genome scale models, will enable C1 chassis to deliver their full potential.